Pharmacokinetic and Pharmacodynamic Interaction between Metformin and Fenofibrate in Animal Models - Ayyanna, Mr. Chakali (Asian Journal of Pharmaceutics (AJP), 2021)
Back ground: Diabetes mellitus and hyperlipidemia are the most common coexisting conditions across the world. Hence, to treat these types of patients both antidiabetic and antihyperlipidemic combination of drugs has to be advised. The most commonly used safe drugs metformin and fenofibrate combination has been selected for our study. Thus, this study was performed to investigate the pharmacokinetic and pharmacodynamic interactions between these two above mentioned drugs in animal models. Materials and Methods: Diabetes and hyperlipidemia in rats were induced by streptozocin and cholesterol rich diet regimen and thereafter treated with metformin and fenofibrate. The blood samples were collected to evaluate plasma drug concentrations using high-performance liquid chromatography. Results: Single dose of metformin and fenofibrate individually and concomitantly treated in diabetic hyperlipidemic rats. Bio-statistically no significant interactions found in pharmacokinetic parameters. In the pharmacodynamic interaction study, the combination therapy of metformin with fenofibrate shown a marked lipid profiles reduction when compared to fenofibrate alone treatment. Conclusion: It is proved in our pharmacodynamic study that concurrent administration of these two drugs has potential benefit in management of diabetes and hyperlipidemia. In addition, due to their in significant pharmacokinetic interaction, the combination therapy will be safe and highly advantageous to the patients.